2023
DOI: 10.3390/ijms24076373
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Demyelination and Remyelination Strategies for Multiple Sclerosis

Abstract: All currently licensed medications for multiple sclerosis (MS) target the immune system. Albeit promising preclinical results demonstrated disease amelioration and remyelination enhancement via modulating oligodendrocyte lineage cells, most drug candidates showed only modest or no effects in human clinical trials. This might be due to the fact that remyelination is a sophistically orchestrated process that calls for the interplay between oligodendrocyte lineage cells, neurons, central nervous system (CNS) resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 124 publications
(185 reference statements)
0
2
0
Order By: Relevance
“…MS is the most common inflammatory autoimmune disease of the CNS, thus leading to demyelinated axons vulnerable to injury and degeneration. Partial restoration of lost OLs and the (re)establishment of myelin sheaths around demyelinated axons can take place through the activation, recruitment, and differentiation of OPCs (Zhao and Jacob, 2023). However, the remyelination of MS lesions often fails (Gruchot et al,FIGURE 4 The absence of autophagy has almost no effect on HSV-1 infection in glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MS is the most common inflammatory autoimmune disease of the CNS, thus leading to demyelinated axons vulnerable to injury and degeneration. Partial restoration of lost OLs and the (re)establishment of myelin sheaths around demyelinated axons can take place through the activation, recruitment, and differentiation of OPCs (Zhao and Jacob, 2023). However, the remyelination of MS lesions often fails (Gruchot et al,FIGURE 4 The absence of autophagy has almost no effect on HSV-1 infection in glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have indicated that blocking LINGO-1 can facilitate the remyelination of axons. However, clinical trials have shown mixed results [ 25 , 26 , 27 ].…”
Section: What Is Multiple Sclerosis?mentioning
confidence: 99%